Antiviral properties of porous graphene, graphene oxide and graphene foam ultrafine fibers against Phi6 bacteriophage - Gungordu Er, Seda; Tabish, Tanveer A.; Edirisinghe, Mohan; Matharu, Rupy Kaur (Frontiers in Medicine, 2022)
As the world has experienced in the Coronavirus Disease 2019 pandemic, viral infections have devastating effects on public health. Personal protective equipment with high antiviral features has become popular among healthcare staff, researchers, immunocompromised people and more to minimize this effect. Graphene and its derivatives have been included in many antimicrobial studies due to their exceptional physicochemical properties. However, scientific studies on antiviral graphene are much more limited than antibacterial and antifungal studies. The aim of this study was to produce nanocomposite fibers with high antiviral properties that can be used for personal protective equipment and biomedical devices. In this work, 10 wt% polycaprolactone-based fibers were prepared with different concentrations (0.1, 0.5,1, 2, 4 w/w %) of porous graphene, graphene oxide and graphene foam in acetone by using electrospinning. SEM, FTIR and XRD characterizations were applied to understand the structure of fibers and the presence of materials. According to SEM results, the mean diameters of the porous graphene, graphene oxide and graphene foam nanofibers formed were around 390 nm, 470nm and 520nm, respectively. FTIR and XRD characterization results for 2 w/w% concentration nanofibers demonstrated the presence of graphene oxide, porous graphene and graphene foam nanomaterials in the fiber. The antiviral properties of the formed fibers were tested against Pseudomonas phage Phi6. According to the results, concentration-dependent antiviral activity was observed, and the strongest viral inhibition graphene oxide-loaded nanofibers were 33.08 ±1.21% at the end of 24 hours.